Video capsule endoscopy in overt and occult obscure gastrointestinal bleeding: Insights from a single‐center, observational study in Japan - Anna Tojo; Tomohisa Sujino; Yukie Hayashi; Kenji J L Limpias Kamiya; Moe Sato; Sakurai Hinako; Yusuke Yoshimatsu; Satoshi Kinoshita; Hiroki Kiyohara; Yohei Mikami; Kaoru Takabayashi; Motohiko Kato; et al. (DEN Open)
Abstract Objective This study aimed to evaluate the use of video capsule endoscopy (VCE) in patients with obscure gastrointestinal bleeding (OGIB), compare cases of overt and occult OGIB, assess the rates of balloon‐assisted enteroscopy (BAE) interventions and rebleeding, and identify predictive markers of positive VCE findings. Methods Medical records of 430 patients who underwent VCE for OGIB between 2004 and 2022 were analyzed. Occult OGIB was defined as IDA or positive fecal occult blood, whereas overt OGIB was defined as clinically imperceptible bleeding. We retrospectively analyzed demographics, VCE findings based on Saurin classification (P0, P1, and P2), outcome of BAE interventions, and rebleeding rates. Results A total of 253 patients with overt OGIB and 177 with occult OGIB were included. P1 findings were predominant in both groups, with a similar distribution. The percentage of patients receiving conservative therapy was higher in P1 than in P2 for both overt and occult OGIB. BAE was more frequently performed in P2 than in P1 VCE (83.0% vs. 35.3% in overt OGIB, 84.4% vs. 24.4% in occult OGIB). The percentage of positive findings and intervention in total BAE performed patients were comparable in P1 and P2 of overt OGIB, whereas these percentages in P2 were more than P1 of occult OGIB. Conclusion VCE effectively identified OGIB lesions requiring intervention, particularly occult OGIB lesions, potentially reducing unnecessary BAE. Rebleeding rates varied according to the VCE findings, emphasizing the importance of follow‐up in high‐risk patients.